PENERAPAN ALAT UKUR SUHU BERBASIS MIKROKONTROLER ARDUINO NANO UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SMP NEGERI 1 SUI KAKAP: Apridiana Ester Manik, Soka Hadiati, Eti Sukadi (JURNAL PENDIDIKAN SAINS DAN APLIKASINYA, 2024)
Abstract The aim of this research is to determine student learning outcomes before and after implementing learning media based on the Arduino Nano microcontroller on temperature material for class VII F SMP Negeri 1 Sui Kakap. This research uses a quantitative approach and uses experimental methods. This experimental research is used to look for certain influences/treatments in research. This research uses a Pre-Experimental Designs (Nondesigns), One-Group Pretest-Posttest Design type of design. The data collection technique used in this research is a measurement technique. The data collection tool used in this research is a multiple choice test. Based on research conducted, the average student learning outcome before the Arduino Nano microcontroller-based temperature measuring instrument was applied was 53.45 with a standard deviation of 9.364, then the average student learning outcome after the Arduino Nano microcontroller-based temperature measuring instrument was applied was 82. 07 with a standard deviation of 6.199. This shows that the application of learning media for temperature measurement tools based on the Arduino nano microcontroller on temperature material has a big influence, this is proven by the value of student learning outcomes. Keywords: Arduino nano microcontroller, learning media and learning outcomes